PROGRESSIVE INTERVIEW LEARNING MODEL AS INNOVATION IN IMPROVING STUDENTS’ LITERACY - Maryam, S (International Journal of Language and Literature, 2018)
This study aims to create a learning model that able to improve students' literacy skills. Within the research method development, the Progressive Interview Learning Model (PILM) has been refined and empowered continuously so the students are gradually treated in the lectures. This study used a total sample, i.e. students who take the Sociolinguistics course. Students are given experience in a structured group. The sample follows lectures with Progressive Interview Learning Model in the classroom, around the campus, and within the community. In the classroom, the interview activity is conducted to college friends about a free topic. In the campus environment, the interview is conducted to structural officials, lecturers, educational staff, and other staff with the topic of information about the lecture smoothness. While in the community, students conduct interviews with community leaders about leadership on religious, economic, security, cultural, social, educational, and community topics. The results showed that students' literacy ability increased significantly.The implication for literacy teacher can be integrated with four language skill in learning.